A Critical Discourse Analysis - Lessu, Deasy Natalia (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2020)
The study is about Critical Discourse Analysis (CDA) which aimed to explore ideology in protest songs of Punk Rock music. The protest emerges due to dissatisfaction with any program or policy of the government or other organization. The musician sees these relevant parties as superior who have overused their power and ideology to control people and cause them suffered. Their music is a representation of their rejection of the condition and the system. Through their lyrics, they intent on raising people’s awareness of the existing issue and persuading them to agree with their beliefs and to fight for a change. The study has to investigate two research questions such as 1) What are the dominant ideologies revealed in Anti-Flag's song lyrics? 2) How are the ideologies revealed in the songs through the use of linguistic features? The study is library research that used CDA and Systemic Functional Grammar (SFG) as basic theories. Under three dimensional framework of CDA: social practice, discourse practice, and textual analysis the study is directed to find out the social issues inside the 15 songs lyrics of Anti Flag and analyze the text with the help of SFG. The significance of this study is that it informs two main ideologies presented in selected songs of Anti-Flag are the anti-authoritarianism: anti-capitalism and anti-nationalism and the social movement and explains how the linguistic features work to present the ideologies.